The Effect of Environmental, Social, and Governance Disclosure on Firm Value: The Moderating Role of Firm Size in Indonesian Energy Companies (2022–2024) - Erlynda Yuniarti Kasim; Daris Aviceena (Journal of Accounting, Management, Economics, and Business (ANALYSIS), 2026)
Purpose: The increasing emphasis on sustainable investment has encouraged investors to evaluate companies based not only on financial performance but also on Environmental, Social, and Governance (ESG) practices. This study examines the effect of ESG Disclosure on firm value, with firm size serving as a moderating variable, in energy sector companies listed on the Indonesia Stock Exchange during the 2022–2024 period. Methodology: This study employed a quantitative approach with an associative research design. Secondary data were obtained from annual reports and sustainability reports. Using purposive sampling, 20 energy sector companies were selected, resulting in 60 firm-year observations. ESG Disclosure was measured using an ESG Disclosure Index, firm value was proxied by Tobin's Q, and firm size was measured by the natural logarithm of total assets. Data were analyzed using multiple linear regression and Moderated Regression Analysis (MRA) with IBM SPSS Statistics 31. Findings: The results reveal that ESG Disclosure has a positive and significant effect on firm value. Moreover, firm size significantly moderates the relationship between ESG Disclosure and firm value, indicating that larger firms are better able to translate ESG initiatives into enhanced corporate value. These findings suggest that effective ESG disclosure supported by greater organizational resources can strengthen investor confidence and improve market valuation. Novelty: This study contributes to the ESG literature by examining the moderating role of firm size in the relationship between ESG Disclosure and firm value within Indonesia's energy sector, which remains relatively underexplored. Significance: The findings provide valuable insights for corporate managers, investors, regulators, and academics in understanding the strategic role of ESG disclosure in enhancing firm value and supporting sustainable business practices.